Development of Free-Range Chicken (Gallus domesticus) Egg Embryos With Brood Incubation and Incubation - Weyni Iskandaria; Syaprina Anggriani; Adella Shaharani; Mira Wahyuni (Jurnal Biologi Tropis, 2023)
Buras chickens (Gallus domesticus) also have several disadvantages, including the difficulty of obtaining good seedlings and lower egg production compared to purebred chickens, relatively slow growth so that the maintenance time is longer. In fact, people like buras chicken because it has high protein and low fat content. The researchers' goal was to look at a comparison of the embryonic development of free-range chickens using incubation and brood hardening for 7 days. The method used is by direct observation through candling which is carried out for 7 days. The treatment was carried out 2 times and the repetition was carried out 3 times. The results found in the development of embryos in hatching devices are not much different from those infested, this could be due to temperature and humidity factors that occur at that time. If the temperature is high (<40̊ C), then the embryo can die, while if the temperature is stable (38-39°C) the embryo can develop quickly.